PROMOSI KESEHATAN TENTANG OBAT AMLODIPIN DAN SIMVASTATIN SERTA CARA PENGGUNAANNYA - Setiawan, Deni; Hadi, Samsul; Sari, Okta Mutia; Mardiati, Nurul; Budi, Muhammad Syihab Setia; Ramadhan, Fery; Hendry, Risye (LPPM Institut Pendidikan Nusantara Global, 2023)
Medicines can interact with food or drink, chemicals or other drugs. Amlodipine is an antihypertensive that is often given with Simvastatin as an antihyperlipidemic. The interaction of amlodipine and simvastatin at a major level can cause an increase in simvastatin levels. The aim of this activity is to provide education about the use of amlodipine and simvastatin in Sekumpul Village, Martapura District. Health promotion will be carried out on Thursday, May 25 2023, at 10.00-13.00 WITA. The education was accompanied by the provision of leaflets containing the definition of interaction. The activity was attended by 21 participants from the elderly group who had used simvastatin, amlodipine or both. The activity ran well and smoothly and succeeded in increasing the participants' knowledge.